Effect of the iris-ciliary angle on the prediction of the vault for phakic implantable collamer lens in the manufacturer’s calculator - Yingjie Ni; Siyuan He; Huihui Jin; Yuanpeng Wu; Yangqi Zhao; Chaoyang Hong; Peijin Qiu; Ting Shen (BMC Ophthalmology)
Abstract Background This study aims to explore the effects of the iris-ciliary angle (ICA) on the accurate prediction of the vault after implantable collamer lens (ICL) using the manufacturer’s online calculation and ordering system (OCOS). Methods The participants were categorized into three groups according to the size of ICA as follows: narrow ICA group (< 40°); normal ICA group (40°-60°); wide ICA group (> 60°). We compared the preoperative ocular characteristics and postoperative vault at 3 months among the three groups. Bivariate correlation was used to analyze the correlation between vault and ICA, and multiple linear regression was used to further analyze the correlation between vault and preoperative parameters. Ordered multicategorical logistic regression analyses were used to further illustrate the effect of different ICA groups on postoperative vault distribution. Results This study included 278 eyes of 157 individuals. There were no statistically significant differences in preoperative ocular parameters among the three ICA groups, while the postoperative vault was minimal in the wide ICA group, followed by the normal and then the narrow ICA group (p < 0.001). The correlation between ICA and vault at 3 months postoperatively was significant in both bivariate correlation and multiple linear regression analysis (both P < 0.001). Ordered multicategorical logistic regression analyses showed that the odds of having a higher vault were 2.586 (P = 0.002) and 5.534 (P < 0.001) times in the normal and narrow ICA groups, respectively, compared to the wide ICA group. Conclusions The size of the ICA has a significant impact on vault created by the recommended ICL size for OCOS. Therefore, ICA should be considered when selecting ICL size using the OCOS recommended sizes preoperatively.